PERAN MAJELIS PENGAWAS DAN KEHORMATAN TERHADAP NOTARIS YANG MEMBUAT AKTA PERJANJIAN NOMINEE - Wikantha, Anak Agung Bagus Maha (University of Merdeka Malang, 2017)
The Notary Supervisory Council and the Notary Public Honor Council (MKN) have not optimally conducted supervision and guidance on notaries in Indonesia. Supervision and guidance only form of sanction is also given uncertain of both institutions to the notary who violates the code of notary ethics related to the making of the nominee agreement. This research analyzes the role of Supervisory Board of Notary and Honorary Board of Notary as well as the form of sanction given to Notary which make deed of nominee agreement. The research method is empirical juridical. The results of the research, MPN’s roles held a hearing to examine notaries and administer administrative sanctions. The role of MKN in solving the case of violation of code of ethics of Notary to Notary which makes nominee agreement very limited, because MKN can only conduct examination. The role of MKN only gives approval or rejection of Notary’s invitation to its presence in the judicial system process. Against a Notary who makes a nominee agreement imposed with civil sanctions, the administration may also be subject to criminal sanctions. The responsibility of a notary is criminally imposed if a notary performs a deed like a fake signature.DOI: https://doi.org/10.26905/idjch.v8i2.1673